2018
DOI: 10.1002/cam4.1580
|View full text |Cite
|
Sign up to set email alerts
|

Value of incorporating newly identified risk factors into risk prediction for chemotherapy‐induced febrile neutropenia

Abstract: Several comorbidities have recently been shown to affect risk of chemotherapy‐induced febrile neutropenia (FN). Here, we evaluated the added predictive value of these comorbidities beyond established FN risk factors. A retrospective cohort study was conducted among adult patients diagnosed with cancer and treated with chemotherapy at Kaiser Permanente Southern California between 2000 and 2009. The study cohort was equally split into training and validation datasets to develop and evaluate the performance of FN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 18 publications
3
14
0
Order By: Relevance
“…Importantly, the previously discussed studies and the majority of published literature regarding patient-specific FN risk factors were developed by studying patients who were not receiving primary prophylaxis. [30][31]37 This study is the first, to our knowledge, to demonstrate the substantial impact of patient-specific risk factors on FN incidence in a population of patients all receiving pegfilgrastim primary prophylaxis in the United States. Because of this, it further validates the importance and absolute necessity of using statistical techniques (eg, propensity score matching) to control for these variables in any real-world study that purports to demonstrate a difference in FN incidence between two pegfilgrastim products.…”
Section: Discussionmentioning
confidence: 81%
“…Importantly, the previously discussed studies and the majority of published literature regarding patient-specific FN risk factors were developed by studying patients who were not receiving primary prophylaxis. [30][31]37 This study is the first, to our knowledge, to demonstrate the substantial impact of patient-specific risk factors on FN incidence in a population of patients all receiving pegfilgrastim primary prophylaxis in the United States. Because of this, it further validates the importance and absolute necessity of using statistical techniques (eg, propensity score matching) to control for these variables in any real-world study that purports to demonstrate a difference in FN incidence between two pegfilgrastim products.…”
Section: Discussionmentioning
confidence: 81%
“…The risk-reducing effect of reduced RDI was consistent with previous reports. 14,15 Finally, among all the pre-treatment laboratory test results, only lower ANC and thrombocyte counts were associated with elevated NI risk in the final model. Similar effects of ANC and thrombocyte counts on the risk of neutropenic complications have been reported also before.…”
Section: Discussionmentioning
confidence: 98%
“…In another observational, prospective study, zaltoprofen in combination with topical anesthetic gel was found to be superior to anesthetic gel alone in controlling cystoscopy-related pain 23. Recently, a study published in Cancer Medicine concluded that zaltoprofen could be a promising drug against the malignant phenotypes in chondrosarcomas via activation of PPAR γ and inhibition of MMP2 activity 24Figure 3Tail flick latency with different drug dosages in tail flick model of pain in mice. Notes: *** represents p -values < 0.001; a denotes NS control at different time intervals, b denotes test and standard drugs compared to NS.…”
Section: Discussionmentioning
confidence: 99%